Self-Care Management dengan Frekuensi Rawat Inap Pasien Hemodialisis - Muhammad Isra’ul Majiid; Dwi Retno Sulistyaningsih; Indah Sri Wahyuningsih (Journal of Health, Medical, and Psychological Studies, 2025)
This study examined the relationship between self-care management and hospitalization frequency among patients receiving maintenance hemodialysis. A quantitative empirical approach with a descriptive correlational cross-sectional design was applied to 99 patients undergoing routine hemodialysis. Self-care management was measured using a validated questionnaire, while hospitalization frequency during the previous year was obtained from medical records. Descriptive analysis demonstrated that a substantial proportion of patients exhibited moderate to high levels of self-care management. Bivariate analysis revealed a statistically significant association between self-care management and hospitalization frequency, indicating that patients with higher self-care capacity experienced fewer hospital admissions. These findings suggest that effective self-care behaviors, including adherence to diet and fluid restriction, vascular access care, and stress management, contribute to greater clinical stability. Integration with existing literature confirms that self-care management operates as a protective behavioral mechanism influencing objective health outcomes in chronic kidney disease. Strengthening self-care management through structured nursing education and supportive interventions may reduce preventable hospitalizations and improve healthcare efficiency for hemodialysis populations. The results provide empirical support for incorporating self-care management as a core component of chronic renal care strategies.